Dental and Maxillofacial Abnormalities in Children with Premature Loss of Primary Canines - Amarelys Morera Pérez; Yuneis Ríos Paz; Diana M Villa Fernández; Arletys Cobas (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
Background: since primary canines are among the last teeth to be replaced by permanent ones, they are critical to maintain the space in the dental arch and proper occlusion. Their premature loss has a greater impact on the anterior region, but it can also affect the posterior region. Objective: to describe dental and maxillofacial abnormalities in children who prematurely lost the primary canines. Methods: a cross-sectional study was conducted in children aged 5 to 9 years attending the Guerrillero Heroico Elementary School located within the health area number 2 of Cienfuegos municipality, from November 2014 through April 2015. Variables analyzed were: age, sex, cause of tooth loss, dental and maxillofacial abnormalities (linguoversion of lower or upper incisors, mesial occlusion, crowding, hyperocclusion, and increased or decreased overjet). Results: the premature loss of primary canines was more frequently observed in children aged 5 and 6 years and in most cases, it resulted from indicated extractions (66.7%). Linguoversion of lower incisors and increased overjet were the most common abnormalities. Conclusion: all children showed dental and maxillofacial abnormalities related to the premature loss of primary canines. This demonstrates the importance of avoiding their early loss whenever possible, as it is a key factor for the development of malocclusion.